TINJAUAN YURIDIS TENTANG RELASI SUAMI-ISTERI MENURUT KHI INPRES NO. 1/1991 - Islamiyati Islamiyati (Masalah-Masalah Hukum, 2013)
Abstract Relationship domicile husband and wife in family represent contractual terms explaining about position of husband and wife as perpetrator in life of family. KHI Inpres No. 1/1991 is as base of yuridis normatif of marriage have arranged detailedly about spouse relationship, consisted of by obligation of husband and wife, dimiciling spouse, husband obligation, habitat, obligation of husband which have the wife to more than a, and the wife obligation. Despitefully, in KHI also discripts  that dimiciling spouse more limber in interpreting leadership of men for woman in family, as in balancing among rights and obligations by proporsional  with hitting creation of family sakinah, mawaddah and rahmah. Keywords : Spouse relationship, KHI Inpres No. 1/1991 Abstrak   Relasi kedudukan suami-isteri dalam keluarga merupakan hubungan hukum yang menjelaskan tentang posisi suami-isteri sebagai pelaku pada kehidupan rumah tangga. KHI Inpres No. 1/1991 sebagai salah satu landasan yuridis normatif perkawinan telah mengatur secara terperinci tentang relasi suami isteri, yang terdiri dari; kewajiban suami isteri, kedudukan suami isteri, kewajiban suami, tempat kediaman, kewajiban suami yang berpoligami, dan kewajiban isteri. Selain itu, dalam KHI juga memaparkan bahwa kedudukan suami isteri lebih lentur dalam mengartikan kepemimpinan laki-laki atas perempuan, yakni keseimbangkan antara hak dan kewajiban secara proporsional demi terciptanya keluarga sakinah, mawaddah dan rahmah. Kata Kunci : Relasi Suami-Isteri, KHI Inpres No. 1/1991